Ad hoc networks : 8th International Conference, ADHOCNETS 2016, Ottawa, Canada, September 26-27, 2016, Revised selected papers /: 8th International Conference, ADHOCNETS 2016, Ottawa, Canada, September 26-27, 2016, Revised selected papers. (2017) - Unknown
No abstract available